Non-conserving exclusion process with a dynamic obstacle. (September 2022) - Pal, Bipasha; Gupta, Arvind Kumar
Abstract: Motivated by complex transport processes occurring in biological and physical systems, we study a non-conserving totally asymmetric simple exclusion process with a dynamic defect particle. The defect particle may appear or disappear stochastically and slows down the traffic of moving particles while bound to the lattice. We analyze the system in the context of mean-field approach, and investigate the steady state properties which exhibit a rich dynamic behavior. The theoretically obtained density profiles and current fully describe the phase diagram, further allowing to elucidate the effect of various dynamics individually. Depending upon non-conserving kinetics and defect dynamics, phase schema displays at most eighteen phases; in total, the system exhibits twenty-one phases. Several critical values of the kinetic rates that trigger a qualitative change in the phase diagrams are obtained using analytical arguments. The theoretical outcomes are validated through extensive Monte Carlo simulations. Highlights: The dynamics of the non-conserving TASEP system with a dynamic defect are investigated. The defect which binds/unbinds on a special site stochastically, modifies the hopping rate of particles to that site. Mean-field analysis is employed and density profiles are obtained analytically. Phase diagrams display a rich structure including mixed phases with a possibility of twenty-one distinct phases. The critical values of parameters that trigger the topological changes in the phase diagrams are theoretically calculated.